2021
DOI: 10.1002/smll.202101084
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of 2D Molybdenum Disulfide Generates Differential Toxicity among Liver Cell Types Compared to Non‐Toxic 2D Boron Nitride Effects

Abstract: 2D boron nitride (BN) and molybdenum disulfide (MoS2) materials are increasingly being used for applications due to novel chemical, electronic, and optical properties. Although generally considered biocompatible, recent data have shown that BN and MoS2 could potentially be hazardous under some biological conditions, for example, during, biodistribution of drug carriers or imaging agents to the liver. However, the effects of these 2D materials on liver cells such as Kupffer cells (KCs), liver sinusoidal endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 71 publications
(149 reference statements)
1
20
0
Order By: Relevance
“…[97] The different uptake mechanisms in the liver cells are further confirmed using MoS 2 and nanocellulose. [109,111] Also, Ouyang et al showed that KCs were taking up NPs via receptor-mediated phagocytosis rather than clathrin-and caveolin-mediated endocytosis or micropinocytosis through localization of NPs by TEM and fluorescent imaging. [115] The difference in uptake mechanisms of cells for NMs would determine their intracellular contents in the liver cells.…”
Section: Cellular Uptake Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…[97] The different uptake mechanisms in the liver cells are further confirmed using MoS 2 and nanocellulose. [109,111] Also, Ouyang et al showed that KCs were taking up NPs via receptor-mediated phagocytosis rather than clathrin-and caveolin-mediated endocytosis or micropinocytosis through localization of NPs by TEM and fluorescent imaging. [115] The difference in uptake mechanisms of cells for NMs would determine their intracellular contents in the liver cells.…”
Section: Cellular Uptake Mechanismsmentioning
confidence: 99%
“…Instead, similar to V 2 O 5 NPs, [ 105 ] MoS 2 ‐Agg induced apoptosis, this is because of the earlier onset of caspase 3/7 activation, while the caspase‐1 activation happened later. [ 111 ] Cao et al also showed the sequestration of protein‐coated 24.5 nm MoS 2 @HSA nanocomplexes by the KCs and the long‐term accumulation of MoS 2 nanodots in the mouse liver. In addition, MoS 2 was oxidized and degraded in the KCs, and the dissolved molybdenum ions were chemically transformed from Mo(IV) to Mo(VI) and used for biosynthesis of molybdenum cofactors (Moco) in hepatocytes as we discussed above.…”
Section: Cell Type‐specific Responses and Molecular Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both liver cell types also showed high expression of the pro-apoptotic protein, Bax, and Cleaved caspase3, and low expression of the anti-apoptotic protein, Bcl-2. ROS induced by nanomaterials is the main mechanism of oxidative stress [ 53 , 54 ], and this process correlates with apoptosis to a certain extent [ 14 , 55 ]. Therefore, ROS levels in the two cells were measured as a proxy for apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It follows that liver is the main member involved in the removal of xenobiotics. The liver is an important metabolic detoxification organ composed of 15% macrophages and 60–80% parenchyma cells [ 13 , 14 ]. Thus, the regulatory role of these cell types in the liver is important for metabolic clearance of exogenous toxins.…”
Section: Introductionmentioning
confidence: 99%